Elementary School Students' Character can be Formed through the Physical Education's Role Teacher - Suprayitno Suprayitno (Randwick International of Education and Linguistics Science Journal, 2023)
The purpose of this study is to ascertain how much physical education teachers contribute to the development of students' character in Tanjung Morawa District elementary/equivalent schools. This study is a quantitative descriptive study that use survey techniques. According to the research that has been done, the sample size for the very high category is 4 persons (67%), for the high category it is 2 people (33%) and for the medium, low, and extremely low categories it is 0 (0%). Based on all the results, it can be said that the character of students in elementary schools or their equivalent throughout the Tanjung Morawa District, which is influenced by the role of the physical education teacher, is good. However, some physical education teachers are still not consistently performing some of the activities listed in the questionnaire.